Effects of Cement Dust Exposure on Malonyldialdehyde Levels and Catalaze Activities in Red Blood Cells - NUR, NAIM; YILMAZ, ABDULKERIM; ERSAN, SERPIL; GULER, NURAN; SUMER, HALDUN; BAKIR, SEVTAP (Asian Journal of Chemistry, 2010)
This study was designed to investigate the plasma oxidant and antioxidant status in both cement plant workers and control subjects. Malonyldialdehyde (MDA) levels and catalaze (CAT) activity were investigated for 42 cement plant workers and the results were compared to 44 control subjects. The MDA levels in erythrocytes were significantly higher in the cement plant workers than in the control group. The CAT activity in the erythrocytes of workers occupationally exposed to cement dust was significantly lower than in the erythrocytes of control group. Occupational exposure to cement dust increased MDA but decreased antioxidant levels in cement plant workers.